Study on laser-induced oxidation modification coupled with micro milling of WC-Co cemented carbide. Issue 7 (May 2020) - Zhao, Guolong; Xia, Hongjun; Li, Liang; Mao, Pengcheng; Du, Yanan; He, Ning
Abstract: Cemented carbide is known as "industrial tooth" and has wide applications in terms of military, aerospace and other fields. In this study, a compound processing approach named laser-induced oxidation modification coupled with micro milling (LCMM) is proposed to solve its poor micro machining performance. The oxidation mechanism of WC-Co cemented carbide is revealed. Surface morphology and cross-section of WC-Co cemented carbide are investigated after laser irradiation under various average laser power and two reaction environment. Research results present that at the average power of 5 W, scanning speed of 0.5 mm/s and oxygen-rich oxygen condition, the laser-induced oxidation process is optimal. The thickness of oxide layer and sub-layer is 9.1 μm and 2.7 μm, and the material surface generates porous and loose oxide layer. In addition, comparative analyses are performed and discussed in detail considering milling force, tool wear and surface quality of machined micro slot. In comparison with conventional micro milling (CONM), cutting force of F x and thrust force of F y generated in removing the oxide layer in LCMM are reduced by 56% and 58% to maximum extent, respectively. The machined surface quality in LCMM is better than that in CONM with a slower rate of increase in surface roughness ( Sa ). At a p = 2 μm and f z = 1.5 μm/z, surface quality of machined micro slot in LCMM is superior to that at other milling parameters, and the surface roughness reach 57 nm. Tool wear rate in LCMM is greatly improved and tool wear mechanism mainly includes slight adhesion wear and abrasion wear. While, in CONM the wear mechanisms are severe abrasion wear, chipping and adhesion wear. The tool service life in LCMM can be promoted more than double.